Validation of a tennis rating score to evaluate the technical level of children tennis players - Šlosar, L.; Šimunic, B.; Pišot, R.; Marusic, U. (Journal of Sports Sciences, 2019)
The purpose of this study was to create a valid and reliable assessment scale for the evaluation of three basic tennis strokes (forehand, backhand, serve) for 6-12-year-old tennis players, named the Tennis Rating Score for Children (TRSC). Altogether 60 players (21: forehand, 22: backhand, 17: serve) were video recorded (30 frames per second) while performing three main tennis strokes and later evaluated using the TRSC by five tennis trainers at Day 1 and Day 7. Agreement between days and raters was examined using the intraclass correlation coefficients (ICC). A Pearson`s correlation was calculated to determine convergent validity (score related to participant`s level of experience). The reliability between raters was very high for all three main strokes (ICCFOREHAND = 0.874; ICCBACKHAND = 0.877; ICCSERVE = 0.877). The intra-rater test-retests ICCs were also very high (ICCFOREHAND = 0.885; ICCBACKHAND = 0.891; ICCSERVE = 0.887). A large (rFOREHAND = 0.660) and very large (rBACKHAND = 0.730; rSERVE = 0.772) Pearson`s correlations were found between all the ratings and the level of experience. The TRSC is shown to be highly reliable and valid when assessing technical skills in novice players, when compared to actual assessment from coaching experts; this tool may be helpful for tennis coaches to make a more objective diagnostic of the technical level of young tennis players.